The use of a P. falciparum specific coiled-coil domain to construct a self-assembling protein nanoparticle vaccine to prevent malaria - Christopher P. Karch; Tais A. P. F. Doll; Sara M. Paulillo; Issa Nebie; David E. Lanar; Giampietro Corradin; Peter Burkhard (Journal of Nanobiotechnology, 2017)
Abstract Background The parasitic disease malaria remains a major global public health concern and no truly effective vaccine exists. One approach to the development of a malaria vaccine is to target the asexual blood stage that results in clinical symptoms. Most attempts have failed. New antigens such as P27A and P27 have emerged as potential new vaccine candidates. Multiple studies have demonstrated that antigens are more immunogenic and are better correlated with protection when presented on particulate delivery systems. One such particulate delivery system is the self-assembling protein nanoparticle (SAPN) that relies on coiled-coil domains of proteins to form stable nanoparticles. In the past we have used de novo designed amino acid domains to drive the formation of the coiled-coil scaffolds which present the antigenic epitopes on the particle surface. Results Here we use naturally occurring domains found in the tex1 protein to form the coiled-coil scaffolding of the nanoparticle. Thus, by engineering P27A and a new extended form of the coiled-coil domain P27 onto the N and C terminus of the SAPN protein monomer we have developed a particulate delivery system that effectively displays both antigens on a single particle that uses malaria tex1 sequences to form the nanoparticle scaffold. These particles are immunogenic in a murine model and induce immune responses similar to the ones observed in seropositive individuals in malaria endemic regions. Conclusions We demonstrate that our P27/P27A-SAPNs induce an immune response akin to the one in seropositive individuals in Burkina Faso. Since P27 is highly conserved among different Plasmodium species, these novel SAPNs may even provide cross-protection between Plasmodium falciparum and Plasmodium vivax the two major human malaria pathogens. As the SAPNs are also easy to manufacture and store they can be delivered to the population in need without complication thus providing a low cost malaria vaccine.